شخصية صالح الشريف التونسي و نشاطه السياسي في المه 1862-1920م - مباركة امال ربحي; د/ محمود بن خليفة (جامعة عمار ثليجي بالاغواط, 2025)
الملخص: ان التاريخ المغاربي تميز بمجموعة من الشخصيات المهمة التي كان لها فضل كبير على شعوبها ومن بين اهم هذه الشخصيات نجد شخصية الشيخ صالح الشريف التونسي الذي تعود أصوله الى الجزائر ولد سنة 1862، نشأ في عائلة علمية، وقد أظهر حبه للجامعة الاسلامية وبدأ بالتفكير في للهجرة الى تركيا فنجح في ذلك وهاجر 1906، حيث تمثل هذه السنة بداية النشاط المهجري له الذي تميز به والذي دام الى غاية 1920. وقد كان هذا النشاط دعائيا بالدرجة الاولى لصالح كل من الدولة العثمانية والمانيا ماإنعكس ايجابيا على زيادة قوتهما بفضل هذا النشاط من خلال اكتساب الدول الخاضعة الاستعمار. Summary : The history of the Maghreb was characterized by a group of important figures who had a great virtue on their peoples, and among the most important of these figures, we find the figure of Sheikh Saleh Al-Sharif Al-Tunisi, whose origins go back to Algeria. Born in 1862, he grew up in a scientific family, and he showed his love for the Islamic University and began thinking about emigrating to Turkey, which he succeeded in doing and emigrated in 1906, where this year marks the beginning of his migratory activity, which was characterized by him and which lasted until 1920 The primary purpose of this activity was propaganda in favor of both the Ottoman Empire and Germany, which positively contributed to strengthening their power through this activity by gaining influence over colonized countri